2020
DOI: 10.1101/2020.03.25.007583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of p67 allelic sequences reveals a subtype of allele type 1 unique to buffalo-derivedTheileria parvaparasites from southern Africa

Abstract: 28East Coast fever (ECF) and Corridor disease (CD) caused by cattle-and buffalo-derived 29 T. parva respectively are the most economically important tick-borne diseases of cattle in 30 the affected African countries. The p67 gene has been evaluated as a recombinant subunit 31 vaccine against East Coast fever (ECF), and for discrimination of T. parva parasites 32 causing ECF and Corridor disease (CD). The p67 allele type 1 was first identified in cattle-33 derived T. parva parasites from east Africa, where para… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 41 publications
4
2
0
Order By: Relevance
“…The current study establishes that although a majority of the cattle in the northern Tanzania region are infected with cattle-transmissible T. parva genotypes, some of the animals are infected with T. parva genotypes with p67 sequences suggesting a likely recent origin from buffalo. This finding generally conforms to the distribution of p67 alleles at the interface area in Kenya that we evaluated (although the buffalo-derived p67 genotypes were different) and also to the situation reported in previous studies (Mukolwe et al 2020;Obara et al 2015;Sitt et al 2019). It is also important to note that this pattern of p67 allelic polymorphism is consistent with a scenario whereby frequent transmission of parasites from buffalo to cattle occurs, but many fail to permanently establish in cattle following initial infection, because insufficient progression of buffalo-derived parasites to the tickinfective erythrocytic piroplasm stage occurs to enable onward transmission between cattle by ticks (Mbizeni et al 2013;Morrison et al 1989).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The current study establishes that although a majority of the cattle in the northern Tanzania region are infected with cattle-transmissible T. parva genotypes, some of the animals are infected with T. parva genotypes with p67 sequences suggesting a likely recent origin from buffalo. This finding generally conforms to the distribution of p67 alleles at the interface area in Kenya that we evaluated (although the buffalo-derived p67 genotypes were different) and also to the situation reported in previous studies (Mukolwe et al 2020;Obara et al 2015;Sitt et al 2019). It is also important to note that this pattern of p67 allelic polymorphism is consistent with a scenario whereby frequent transmission of parasites from buffalo to cattle occurs, but many fail to permanently establish in cattle following initial infection, because insufficient progression of buffalo-derived parasites to the tickinfective erythrocytic piroplasm stage occurs to enable onward transmission between cattle by ticks (Mbizeni et al 2013;Morrison et al 1989).…”
Section: Discussionsupporting
confidence: 92%
“…The fact that we did not detect the buffalo-derived allele type 4 of p67in our buffalo samples may have been the result of under sampling; hence, further in-depth sampling will improve the understanding of allele distribution patterns in the region. Previous analyses had suggested that this allele, which has been found in buffalo T. parva in South Africa, seems to be rare within East Africa (Mukolwe et al 2020;Obara et al 2015;Sibeko et al 2010;Sitt et al 2019). By contrast, buffalo-derived T. parva alleles 2 and 3 genotypes which we found in our Kenyan sample dataset were also reported in previous studies (Obara et al 2015;Sitt et al 2019), but not observed in the Tanzanian cattle samples studied.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations